The Finnish solution to final disposal of spent nuclear fuel - Vehmas Jarmo; Rentto Aleksis; Luukkanen Jyrki; Auffermann Burkhard; Kaivo-oja Jari (Springer VS, 2025)
Fortum Oyj and Teollisuuden Voima Oyj (TVO), the two companies that own the operating units in Finnish nuclear power plants, in 1996 formed a joint company, Posiva Oy, to deal with their nuclear wastes. This includes both the low- and medium-level radioactive waste and the high-active used nuclear fuel. Several locations were considered before the choice of Olkiluoto in 1999 and its acceptance by the municipality of Eurajoki in 2000. In 2010, the Finnish Government granted a decision-in-principle required by the Finnish Nuclear Act to Posiva Oy regarding the construction of a final disposal site for nuclear wastes including the above-ground encapsulation plant and the final disposal facility called Onkalo. In 2015, the Government granted the construction licence for this entity to be built. The site already includes the operating nuclear power plants (OL-1 and OL-2) of TVO and the OL-3 unit which has been under construction since 2005 and shall be taken into use in 2022. After several delays this is the timetable according to the most recent information in early Spring 2021 provided by TVO. Thus, Finland is the first country in the world to enter the implementation phase of spent nuclear fuel. A future challenge is the nuclear waste of possible new nuclear power plants not included in the plans of Posiva Oy.
The Future of Radioactive Waste: Lessons from Europe